HUBUNGAN WAKTU REAKSI DAN POWER OTOT TUNGKAI DENGAN KECEPATAN TENDANGAN SAMPING(T) PESILAT REMAJA PUTRA PERGURUAN SATRIA MUDA INDONESIA KECAMATAN DAYUN - Kusniah, Siti; Zainur, Zainur; Vai, Aref (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: The problem of this research is that there is still a lack of speed in the side kicks of male fighters in the Indonesian young warrior college. The purpose is to prove whether there is a relationship between reaction time and leg muscle power with the speed of the side kick of a male teenager in the Indonesian young warrior college in the subdistrict of Dayun, so that when doing side kicks fighter can hit opponents and make it difficult for opponents to counterattack. This research technique uses total sampling, where the total population is sampled. This study uses correlation techniques. Then, the test data used the normality test, the moment correlation product test, a significant test α = 0.05. The normality test variables X1, L0max (0.0945) <Ltabel (0.319), X2, L0maks (0.1271) <Ltabel (0.319), and the normality test Y, L0max (0.2307) <Ltabel (0.319) in other words 95% confidence level of normal data and research conclusions show: where there is a significant relationship between reaction time and leg muscle power with side kick speed with a correlation r = 1,306 where r count (1,306)> r table (0,878). Where the large correlation coefficient when viewed from the level of relationship (interpretation) the value of r is having a very strong level of correlationwith the interpretation of the r value of 0.80 – 1,000.Key Words: Correlation, Reaction Time, Leg Muscle Power, Side Kick Speed